2022
DOI: 10.3389/fcimb.2022.899702
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-Epidemiology Aspect of Inpatients With Moderate or Severe COVID-19 in a Brazilian Macroregion: Disease and Countermeasures

Abstract: COVID-19, also known as coronavirus disease 2019, is an infectious viral disease caused by SARS-CoV-2, a novel coronavirus. Since its emergence, its epidemiology has been explored; however, for some regions of the world, COVID-19’s behavior, incidence, and impact remain unclear. In continental nations like Brazil, this lack of knowledge results in nonuniform control, prevention, and treatment measures, which can be controversial in some locations. This study aimed to describe the epidemiological profile of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Prospective observational study in the United Kingdom reported lower prevalence in the loss of smell, less involvement of the lower respiratory tract, and a shorter period of illness in Omicron variants compared with Delta variant infections [8]. The clinical manifestations and epidemiological aspects of COVID-19 have been extensively reported in various regions around the world [9]. The SARS CoV-2 Omicron variants in Bangladesh have not been evaluated with respect to the COVID-19 outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Prospective observational study in the United Kingdom reported lower prevalence in the loss of smell, less involvement of the lower respiratory tract, and a shorter period of illness in Omicron variants compared with Delta variant infections [8]. The clinical manifestations and epidemiological aspects of COVID-19 have been extensively reported in various regions around the world [9]. The SARS CoV-2 Omicron variants in Bangladesh have not been evaluated with respect to the COVID-19 outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, disease's outcomes are influenced not only by viruses' strains, but also by health individualities and social context, and Silva et al, (2022) did not find that sex and chronic diseases were significant death predictors in their study in Uberaba, Minas Gerais. Conversely, the study found a 40% increase in the odd of death for every 10 years of life, and the high mortality among the elderly could have hindered the mortality related to sex and chronic diseases (Silva et al, 2022). Therefore, local studies focusing on specific populations are important for better health management and public policies designing.…”
Section: Discussionmentioning
confidence: 97%
“…The clinical form of COVID-19 presents itself in an extensive range of symptoms (Sofi et al, 2020;WHO, 2022), being the Severe Acute Respiratory Syndrome an acute form with devastating effects worldwide. Brazil was largely affected by the disease, with high trends of lethality and a considerable burden on its hospital systems (Silva et al, 2022;Zeiser et al, 2022). This study evaluated the epidemiological aspects and factors associated to death in hospitalized patients in the municipality of Contagem, the third most populous in the State of Minas Gerais.…”
Section: Discussionmentioning
confidence: 99%